Arts-Based Learning Environment Management for Early Childhood Creativity: A Literature Study - Nurlina Nurlina (Universitas Negeri Surabaya, 2026)
This study aims to analyze the role of art-based learning management in supporting the development of creativity in Early Childhood Education. Creativity is an important aspect of children's development that needs to be stimulated through meaningful learning experiences. This study uses a literature study method by analyzing 20 scientific articles obtained from Google Scholar, ERIC, and Scopus databases. The search process was carried out using the keywords arts-based learning, learning environment, creativity, early childhood education, and learning management. The results show that art-based learning contributes significantly to increasing children's creativity, especially if supported by effective learning management, a conducive learning environment, and innovative approaches. The integration of art in learning also has an impact on children's cognitive, social-emotional, and self-expression development. This study concludes that art-based learning needs to be managed systematically and integrated in Early Childhood Education to optimize children's creative potential. Further research is suggested to test its effectiveness through empirical studies in the field.